Mitigation of the anchoring effect in an electronic audit setting. - Chen, Yingtong. (2008)
Our study examined whether anchoring effect could be aggravated in an electronic audit setting and the extent forewarning could mitigate the bias. Results revealed that auditors’ control risk assessments exhibited the anchoring effect. Forewarning failed to mitigate the bias, but an additional reminder to the forewarning successfully attenuated the bias.